The Influence Of Tax Knowledge And Information Technology On The Compliance Of Land And Building Taxpayers PBB-P2 (A Case Study In Surian Period 2021-2024) - Handi, Handi; Kurniawan, Ryan Feryana; Mariana, Syafira (Journal of Business, Accounting and Finance, 2025)
Rural and Urban Land and Building Tax is a tax imposed on the ownership or use of land and buildings located in rural and urban areas.Tax plays an important role as the main source of state revenue used to fund various public expenditures, such as infrastructure, education, health, and security.The purpose of this study was to determine the effect of tax knowledge and information technology on the compliance of Rural and Urban Land and Building Tax (PBB-P2) both partially and simultaneously. The research method used is a quantitative descriptive approach method. Data collection techniques were obtained from the results of questionnaires and literature studies. The sample in this study were taxpayers in Surian District, Sumedang Regency, totaling 100 respondents. The analysis technique used was multiple linear regression analysis. The data collected were calculated using the SPSS 23 for Windows program. Based on the results of the data analysis, it can be concluded that partially tax knowledge has a positive effect on the compliance of rural and urban land and building taxpayers by 22.4% and information technology has a positive effect on the compliance of rural and urban land and building taxpayers by 32.2%. Simultaneously, tax knowledge and information technology have a positive influence on the compliance of rural and urban land and building taxpayers by 54.5% and the remaining 45.5% is influenced by other factors outside this research